Gambaran Hasil CT-Scan Toraks pada Pasien Coronavirus Disease 2019 (COVID-19) - Malaru, Claudia R. E.; Rondo, Alfa G. E. Y.; Wagiu, Christilia G. (Universitas Sam Ratulangi, 2021)
Abstract: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Indonesia reported its first case in March 2, 2020. Cases are increasing and spreading rapidly throughout Indonesia. One of the main imaging modalities for examination of COVID-19 is chest computed tomography scan (CT-scan) which plays an important role in detection, evaluation of severity, and follow-up of disease course. This study was aimed to obtain the description of CT scan results in patients with COVID-19. This was a literature review study using three databases, namely Pubmed, ClinicalKey, and ScienceDirect. The keywords used were COVID-19 AND Chest CT. Based on inclusion and exclusion criteria, there were 10 literatures selected. It was found that chest CT results could accurately evaluate the features and extent of lung lesions. The typical CT-scan results were ground-glass opacities (GGO), GGO with mixed consolidation, adjacent pleural thickening, interlobular septal thickening, and air bronchogram. Based on age, sex, and comorbidities, there was not any significant differences in chest CT findings. In conclusion, GGO, air bronchogram, and consolidation were found in chest CT-scan of COVID-19 patients. Meanwhile, based on age, sex, and comorbidities there were no significant differences in chest CT-scan.Keywords: COVID-19, chest CT-scanÂ Abstrak: Coronavirus disease 2019 (COVID-19) merupakan suatu penyakit menular yang disebabkan oleh severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Indonesia melaporkan kasus pertama pada tanggal 2 Maret 2020. Kasus meningkat dan menyebar dengan cepat di seluruh wilayah Indonesia. Salah satu modalitas pencitraan utama yang menjadi pilihan untuk pemeriksaan COVID-19 ialah Computed Tomography Scan (CT-scan) toraks yang berperan penting dalam deteksi, evaluasi keparahan, dan tindak lanjut perjalanan penyakit. Penelitian ini bertujuan untuk mengetahui gambaran hasil CT-scan pada pasien COVID-19. Jenis penelitian ialah literature review dengan pencarian data menggunakan tiga database yaitu Pubmed, ClinicalKey, ScienceDirect. Kata kunci yang digunakan yaitu COVID-19 AND Chest CT. Hasil seleksi berdasarkan kriteria inklusi dan eksklusi mendapatkan 10 literatur. Didapatkan hasil CT-scan toraks dapat secara akurat mengevaluasi fitur dan luas lesi paru dan CT-scan yang khas ialah ground-glass opacities (GGO), GGO dengan konsolidasi campuran, penebalan pleura yang berdekatan, penebalan septum interlobular, dan bronkogram udara. Pada temuan CT-scan toraks berdasarkan usia, dan jenis kelamin tidak didapatkan perbedaan bermakna. Simpulan penelitian ini ialah terdapat GGO, air bronchogram, dan konsolidasi pada CT-scan toraks pasien COVID-19 sedangkan berdasarkan usia, jenis kelamin, dan komorbid tidak ditemukan perbedaan bermakna.Kata kunci: COVID-19, CT-scan toraks